Management science in Malaysia - Aziz A. Hamid; Hamdan Ariffin; R. Nooraini R. Shamsuddin (Penerbit Universiti Kebangsaan Malaysia, 1982)
This study discusses findings of a sample survey on the application of Management Science and Operations Research techniques in Malaysia. The objective of the study is to determine the extent of current and future application of these techniques. The findings indicate that current applications are limited to the use of techniques which do not require adoption of advanced mathematical models, such as finuncial models. forecasting techniques, and simple techniques involved in project planning. Similar applications are forseen in the future.